(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Novel therapeutic strategy in radionuclide therapy use cell-penetrating monoclonal antibodies to carry Auger-emitting radionuclides into the cells. Estimation of dose in normal and tumor cells are important to investigate the efficacy and toxicity of treatment. Monte Carlo simulation is the most suitable method for estimation of absorbed dose at microscopic level. It is therefore useful to carry out Monte Carlo simulation of Auger emitting radionuclides in order to assess the sensitivity of the results with respect to transport approximations generally used in Monte Carlo codes. There are several Auger emitting radionuclides with potential clinical applications, however, based on their half-life 111In is the most suitable for Auger therapeutic purposes and was considered in the present investigation. Geant4 Monte Carlo simulation was performed and specific absorbed dose fraction (or S-values) for 111In were calculated by using different physics model (Standard, Livermore, Penelope and Geant4-DNA) and compared with Medical Internal Radiation Dosimetry (MIRD) S-values. Source was distributed in the cytoplasm (Cy), surface (Cs) and nucleus (N). Average of relative differences (RD) (%) were calculated for self and cross absorbed dose. RD(%) for self-absorption (NßN) were 4.4, 2.36, 6.21 and 1.1 for Standard, Penelope, Livermore and Geant4-DNA respectively. For cross-absorption these values were higher (e.g. for NßCy 15.4, 18.36, 19.21 and 24.8 for Standard, Penelope, Livermore and Geant4-DNA respectively). Cutoff energy considered for electrons and gamma photons affect the results in dose estimation for Auger electrons in Monte Carlo simulation.